Implementation fidelity of an Integrated Healthy Lifestyle Service: a process evaluation. (September 2022) - Sanders, GJ; Griffiths, C; Flint, S; Christensen, A; Gately, P
Aims: The current study aimed to evaluate implementation fidelity of an Integrated Healthy Lifestyle Service (IHLS). Methods: A pragmatic sample of 28 individual interviews and 11 focus groups were conducted. This resulted in a total of 81 (22 male) individuals comprising key stakeholders (n = 18), as well as intervention staff across senior management (n = 4), team lead (n = 14) and practitioner (n = 11) roles, and intervention clients (n = 34). Results: A mixed degree of implementation fidelity was demonstrated throughout the five a priori fidelity domains of study design, provider training, intervention delivery, intervention receipt, and enactment. Stakeholders, staff and clients alike noted a high degree of intervention receipt across all services offered. Contrastingly, practitioners noted that they received minimal formal operational, data systems, clinical, and curriculum training as well as a lack of personal development opportunities. Consequently, practitioners reported low confidence in delivering sessions and collecting and analysing any data. A top-down approach to information dissemination within the service was also noted among practitioners which affected motivation and overall team morale. Conclusion: Results can be used to conceptualise best practices as a process to further strengthen the design, delivery and recruitment strategies of the IHLS.